Youth culture in China : from Red Guards to netizens - Clark, Paul (Cambridge University Press, 2012)
"The lives and aspirations of young Chinese (those between 14 and 26 years old) have been transformed in the past five decades. By examining youth cultures around three historical points - 1968, 1988 and 2008 - this book argues that present-day youth culture in China has both international and local roots. Paul Clark describes how the Red Guards and the sent-down youth of the Cultural Revolution era carved out a space for themselves, asserting their distinctive identities, despite tight political controls. By the late 1980s, Chinese-style rock music, sports and other recreations began to influence the identities of Chinese youth, and in the twenty-first century, the Internet offers a new, broader space for expressing youthful fandom and frustrations. From the 1960s to the present, this book shows how youth culture has been reworked to serve the needs of the young Chinese"--